Investigating the potential of Zn2+, Cd2+ and Ni2+ substituted bismuth magnesium tantalate pyrochlores as a new class of ceramic dielectrics - Khaw, C.C.; Tan, P.Y.; Tan, Kar Ban; Chan, K.Y.; Murthy, H.C. Ananda; Balachandran, R.; Chen, S.K.; Kechik, M.M.A.; Lee, O.J.; Lu, M. (Elsevier, 2025)
This study examined the impact of zinc (Zn), cadmium (Cd) and nickel (Ni) transition metals on the formation, structure and dielectric properties of bismuth magnesium tantalate (BMT) pyrochlores. A one-to-one substitution of Mg2+ with Zn2+, Cd2+ and Ni2+ in BMT pyrochlore was proposed, with Zn2+ (0.74 Å) and Ni2+ (0.69 Å) substituting the 6-coordinated B-site Mg2+ (0.72 Å), while Cd2+ (1.10 Å), possessing a similar ionic radius to Bi3+ (1.17 Å), replaced Mg2+ (0.90 Å) at the 8-coordinated A-site. The resulting doped BMT pyrochlore solid solutions adhered to the formulas: (Bi3.5Mg0.5)(Mg1.3-xZnxTa2.7)O13.8 (0 ≤ x ≤ 0.6), (Bi3.5Mg0.5)(Mg1.3-xNixTa2.7)O13.8 (0 ≤ x ≤ 0.1) and (Bi3.5Mg0.5-xCdx)(Mg1.3Ta2.7)O13.8 (0 ≤ x ≤ 0.1). X-ray diffraction (XRD) confirmed their phase purity, with lattice parameters ranging from 10.5515 (10) to 10.6312 (21) Å. Notably, grain size remained consistent (1.3–22.4 μm) across these modified BMT pyrochlores, exhibiting relative densities ≥90 % of the theoretical value. Scherrer and Williamson-Hall analyses indicated crystallite sizes within the 31–68 nm range. Furthermore, thermal stability was confirmed over ∼30–1000 °C due to the absence of thermal events. The Ni-doped BMT pyrochlore (x = 0.1) demonstrated enhanced conductivity (activation energy, Ea = 1.38 eV) compared to the undoped material (Ea = 1.47 eV). Conversely, Zn- and Cd-doped BMT pyrochlores showed reduced conductivity (Ea ≈ 1.53 eV and 1.51 eV, respectively) with increasing dopant concentration. Specifically, Zn-doped (x = 0.6) and Cd-doped (x = 0.1) BMT exhibited favourable dielectric properties: moderately high dielectric constants (ε′ ≈ 80), low dielectric loss (tan δ ≈ 2 x 10−3) and a low temperature coefficient of dielectric constant (TCε' ≈ −200 to −240 ppm/°C), making them suitable for ceramic capacitor applications.